Activation and Characterization of Lanthomicins A–C by Promoter Engineering in Streptomyces chattanoogensis L10 - Liu, Xiao-Fang; Wang, Jun-Xiao; Chen, Xin-Ai; Liu, Yu; Li, Yong-Quan (Frontiers in Microbiology, 2022)
The emergence of drug resistance highlights the importance of new drug discovery. Microbial secondary metabolites (SMs) encoded in biosynthetic gene clusters (BGCs) are a prolific source of drugs, whereas most of these BGCs are cryptic. Thus, taking strategies to activate these cryptic BGCs is of great importance for potential drug discovery. In this work, three novel pentangular polyphenols lanthomicin A-C were identified by activating a cryptic aromatic polyketide BGC through promoter engineering combined with optimization of fermentation conditions. We further confirmed the involvement of lanthomicin (ltm) BGC in the biosynthesis by CRISPR-Cpf1 assisted gene editing. Based on functional analysis of homologous genes, a putative biosynthetic pathway was proposed for the three lanthomicins. Particularly, lanthomicin A showed anti-proliferative activity with IC50 0.17 μM for lung cancer cell line A-549. The discovery of lanthomicins brings new members to the pentangular polyphenol subclade of aromatic polyketide and demonstrates the potential of Streptomyces as a source for drug discovery.